GIRAFE v1: a global climate data record for precipitation accompanied by a daily sampling uncertainty - H. Konrad; R. Roca; A. Niedorf; S. Finkensieper; M. Schröder; S. Cloché; G. Panegrossi; P. Sanò; C. Kidd; C. Kidd; R. A. Jucá Oliveira; R. A. Jucá Oliveira; et al. (Earth System Science Data)
Here, we introduce the first version of the Global Interpolated RAinFall Estimation (GIRAFE v1), the first dedicated global climate data record for precipitation by the Satellite Application Facility on Climate Monitoring (CM SAF) of the European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT). GIRAFE is based on precipitation rate estimates obtained from observations by a variety of passive microwave (PMW) radiometers on board low-Earth orbit satellites and related retrieval algorithms and frequent and highly resolved infrared observations from geostationary satellites covering all longitudes and used at latitudes below 55° N/S. At higher latitudes, only the PMW-based precipitation rates are utilised. GIRAFE v1 is available globally at 1° resolution as daily accumulations and monthly means for the years 2002–2022, with an implementation of continuous production planned for 2025 onwards. The daily product is accompanied by a dedicated sampling uncertainty estimate based on decorrelation scales in space and time in infrared-based instantaneous precipitation fields. The methods for the generation of GIRAFE v1 are described in detail, followed by the results of quality assessment and intercomparison activities. GIRAFE v1 reproduces reference datasets with a performance similar to that of established precipitation products, especially those that are – like GIRAFE v1 – not adjusted to ground-based observations. Likewise, GIRAFE v1 proves to be suitable for the analysis of regional precipitation extremes, e.g. in their relation to sea surface temperatures. The main objective in the production of GIRAFE v1 is climate applications, for which we find the dataset highly suitable according to the stability and homogeneity analysis. The GIRAFE v1 data record is hosted by CM SAF and is freely available at https://doi.org/10.5676/EUM_SAF_CM/GIRAFE/V001 (Niedorf et al., 2024a).